Prediction of PID control model on PLC - Erwani Merry Sartika; T. Rudi Sarjono; Diki Dwi Saputra (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
PID (Proportional Integral Derivative) is a control algorithm that mostly used in industry. However, users have never known what the PID model that used inside the PLC. By knowing the PID model that used in PLC, users will have more choice in determining the more appropriate tuning algorithm. Also, users can use MATLAB to perform analysis and can implement it to PLC. Through OPC Server (Object Linking and Embedding for Process Control Server) as a software interface, programs on a windows operating system can communicate with industry devices universally. PID model prediction method is done by comparing the output of the plant controlled by PID model in PLC and PID model in SIMULINK MATLAB using OPC Server intermediaries. Based on comparison result in graph and analysis using integral error method, PLC M221 using Parallel PID model and PLC S7-1200 using Ideal PID model.